2015
DOI: 10.1111/iej.12516
|View full text |Cite
|
Sign up to set email alerts
|

Guided access cavity preparation using cone‐beam computed tomography and optical surface scans – an ex vivo study

Abstract: The combined use of CBCT and optical scans for the precise construction of a guide rail led to a drill path with a precision below a risk threshold. The present technique may be a valuable tool for the negotiation of partial or complete pulp canal obliteration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
92
0
21

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(128 citation statements)
references
References 16 publications
6
92
0
21
Order By: Relevance
“…Buchgreitz et al . () found the mean deviation of the access cavities to be lower than the 0.7‐mm threshold defined by the radius of the bur plus the radius of the root canal. Zehnder et al .…”
Section: Review Of Endodontic Applicationsmentioning
confidence: 94%
See 1 more Smart Citation
“…Buchgreitz et al . () found the mean deviation of the access cavities to be lower than the 0.7‐mm threshold defined by the radius of the bur plus the radius of the root canal. Zehnder et al .…”
Section: Review Of Endodontic Applicationsmentioning
confidence: 94%
“…In ex vivo investigations of accuracy, Buchgreitz et al . (), Zehnder et al . () and Connert et al .…”
Section: Review Of Endodontic Applicationsmentioning
confidence: 96%
“…Additionally, a commercially available bur was used instead of a specially adapted bur (Buchgreitz et al . , Connert et al . , ).…”
Section: Discussionmentioning
confidence: 99%
“…By using a 3D‐printed guide, the chances of iatrogenic damage to the root are reduced and the likelihood of finding the root canal is high, whilst also reducing treatment time (Buchgreitz et al . , Krastl et al . , van der Meer et al .…”
Section: Introductionmentioning
confidence: 99%
“…They found a 0.99 mm horizontal deviation (ranging from 0.0 to 6.5 mm) at the level of the implant platform of the osseointegrated implants, a 1.24 mm horizontal deflection (ranging from 0.0 to 6.9 mm) at the osseointegrated implant apex and an average angle deviation of 3.81° (ranging from 0.0° to 24.0°) to the longitudinal osseointegrated implant axis . Buchgreitz et al evaluated ex vivo the accuracy of a preparation procedure planned for teeth with root canal obliteration using a guide rail concept based on CBCT scan merged with an optical surface scan and the mean distance between the drill path and the target was significantly lower than 0.7 mm and Zehnder et al concluded that deviations of planned and prepared access cavities were low with means ranging from 0.16 to 0.21 mm for different aspects at the base of the bur and 0.17–0.47 mm at the tip of the bur and the mean of angle deviation was 1.81° . In the field of endodontics, the use of guided splints assisted by CBCT has been documented for treating dens invaginatus and teeth with root canal calcification and apical pathology; this lack of precision can make it difficult to locate the root canals and may lead to unexpected complications.…”
Section: Discussionmentioning
confidence: 99%